Novel reversible, irreversible and fluorescent inhibitors of platelet-activating factor acetylhydrolase as mechanistic probes - Deigner, Hans-Peter; Kinscherf, Ralf; Claus, Ralf; Fyrnys, Beatrix; Blencowe, Christopher (Atherosclerosis, 1999)
Phosphatidylcholines (1-O-alcoxy-2-amino-2-desoxy-phosphocholines and 1-pyrene-labeled analogs) were synthesized and used to examine interactions with recombinant human PAF-acetylhydrolase (PAF-AH), an enzyme purified from plasma, and with macrophage-like U937 cells. Novel phosphatidylcholines containing a sn-2-carbamoylester group such as 1-O-hexadecyl-2-desoxy-2-amino-methylcarbamoyl-2-methyl-rac-glycero-3-phosphocholine 11 were found to act as site-specific irreversible enzyme inhibitors with Ki-values up to 83 (Kirev) and 177 (Ki(inact)) μm. The compounds exhibit only marginal inhibition of Ca2+-dependent phospholipases. Kinetic data show that phosphocholines carrying a terminal sn-1-pyrene moiety inhibit PAF-AH activity with an effectivity similar to analogs with an aliphatic chain. 1-O-Decyloxy-[10-(4-pyrenyl)-butoxy]-2-desoxy-2-amino-carbamoyl-methyl-rac-glycero-3-phosphocholine 13 could be used for enzyme labeling and to demonstrate an inhibitor-enzyme stoichiometry of 0.7:1. At 8°C, the compound accumulated in the membranes of U937 cells, at 37°C it was internalized into intracellular compartments. Structure-activity studies in a mixed micelle assay indicated that the inhibition power of reversible and irreversible inhibitors increases along with the (sn)-1-chain length similar to the structure-dependent binding of ether phospholipids to the PAF-receptor. Unlike the situation at the (sn)-1-position, increasing chain length at the sn-2-position, or an alkyl branching of the glycerol backbone significantly reduced the inhibitory potency.
Gesehen am 14.09.2017